Bridging Transformation in a PDS Preservice Teacher Education Program - Holly Klock (Adult Education Research Conference, 2019)
This empirical work explores Transformational Learning within preservice teacher education. Self-identified disorienting dilemmas are a catalyst for communicative discourse in which preservice teachers approach learning by problematizing biases and assumptions.
Keywords: preservice teacher education; transformational learning